Analysis of Sulfate and Cadmium Distribution in Groundwater in Wonocolo Traditional Oil Mining Area, Bojonegoro Regency - Santi Amanda Tiara Putri; Nindy Callista Elvania; Heri Mulyanti (Advances in Tropical Biodiversity and Environmental Sciences, 2025)
Wonocolo Village in Bojonegoro Regency is one of the traditional oil mining areas that still contains old Dutch oil wells. The presence of these wells has the potential to affect groundwater quality. Petroleum that contaminates the soil can seep into groundwater, posing a serious threat to areas that rely on it as a source of clean water. This study aims to evaluate groundwater parameters, including temperature, pH, cadmium, and sulfate, by the standards set by the Indonesian Ministry of Health Regulation No. 32 of 2017, specifically regarding hygiene, sanitation, and public baths. Sampling was conducted using a purposive sampling method at 14 points. Data analysis was performed using the inverse distance weighted (IDW) interpolation method. The results showed that in the densely populated southern part of the study area, the temperature at sampling point SG 13 reached 35°C, and cadmium levels across all samples ranged from 0.059 to 0.156 mg/L, exceeding the permitted quality standards. In contrast, pH and sulfate values met the quality standards set by Permenkes No. 32 of 2017. Therefore, efforts are necessary to reduce cadmium levels in the groundwater of Wonocolo Village, Bojonegoro Regency.